Application of multi-species microbial bioassay for toxicity risk assessment LumiMARA luminometric tests and chemical analyses to assess water quality in the świętokrzyskie voivodeship - Robert Kowalik; Małgorzata Widłak; Monika Metryka-Telka; Renata Stoińska; Grzegorz Czerwonka (Desalination and Water Treatment, 2024)
The area of Świętokrzyskie voivodeship is located within the range of several macro-regions, the parent rocks are highly differentiated, which affects the diversity of soil and water conditions. and water conditions. The weakest soils occur in the central and northern parts, the best soils in the eastern and southern parts of the Świętokrzyskie Voivodeship. The study presents selected physicochemical properties of groundwaters captured by borehole wells and spring waters in selected areas of the and spring waters in selected areas of the swietokrzyskie voivodeship. The analysed water was subjected to toxicity analysis using multispecies LumiMARA test (Microbial Assay for Risc Assessment) and physicochemical parameters were determined - pH, carbonate hardness and total hardness, conductivity, OWO and chlorides. The water samples for the study were collected at different times of the year 2021- January, April, July, November. The conductivity of the tested waters, regardless of the source of origin, varies by location. The aim of the study was to analyze the quality of water due to ground and water conditions and very high interest and use of water from the studied sources by the inhabitants of the regions. The study showed that the analysed waters contained toxic substances in concentrations exceeding the WHO recommendations. Chemical analyses were reflected in ecotoxicological analyses, which showed toxic effects on individual bacterial strains and allowed the waters to be classified into individual toxicity classes.